2017
DOI: 10.1155/2017/1401503
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deposition of Zinc Oxide on the Surface of Composite Membrane Polysulfone-Graphene-Polystyrene in the Presence of Water Soluble Polymers

Abstract: The aim of this study consisted in the development of an alternative synthesis procedure for hybrid ultrafiltration membranes for water purification. The membranes were obtained by wet-phase inversion method based on aliquots of polysulfone (PSF) and graphene nanoplatelets modified with poly(styrene) (G-PST). The hybrid materials were modified by electrochemical deposition of zinc oxide (ZnO) on one side of the membranes in the presence of water soluble polymers. Raman, XPS, and TGA analyses were used to chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The shrinkage proportion is under 60% in these membranes, which is more effective for filtration. [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shrinkage proportion is under 60% in these membranes, which is more effective for filtration. [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
“…The shrinkage proportion is under 60% in these membranes, which is more effective for filtration. [35] The performance of the synthesized membrane in water purification was measured by calculating their solvent content. Different solvents in polarity from propanol to water were selected to determine the solvent absorption capacity of the hybrid membrane.…”
Section: Permeation Studies Of the Pvdf/pani Hybrid Membranesmentioning
confidence: 99%
“…They used wet-phase inversion method with polysulfone and graphene nanoplatelets modified with poly (styrene) to obtain their membranes. ZnO was deposited on one surface of the membrane with polymers that are soluble in water [39]. In the study reported by Igbinigun and others, the modified GO-membrane showed 2.6 times better flux recovery compared to the unmodified membrane and this shows that it is wise to modify membrane with GO to increase flux recovery.…”
Section: Ultrafiltration (Uf)mentioning
confidence: 95%